Video Terjadinya Petir Sebagai Media Pembelajaran Fisika Untuk Meningkatkan Pemahaman Konsep Siswa pada Materi Listrik Statis - ’Ula, Indra Rahmatul; Sutikno, Sutikno; Masturi, Masturi (PROSIDING SEMINAR NASIONAL FISIKA (E-JOURNAL), 2015)
This study aims to (1) the effect of the use of video as a medium for the occurrence of lightning physics learning to improve the understanding of the concept of static electricity on the material. This research is descriptive kuantiatif. The data collection techniques using kuesioner.Instrumen technique used is the question sheet. Sheets question is in the form of questions given before and after implementing the concept of learning to know the students’ understanding. Sheets, there are two questions about the package, which package before implementation of learning about and booklet implemented after learning to determine the increase students’ understanding of the static electricity. The population is class 9 SMP Nusa Bangsa Demak. Determination of the samples was done by cluster random sampling technique. Data analysis was carried out quantitatively so that the known increase in understanding of concepts in students. Based on the analysis of data obtained by the experimental class that there is a significant increase between the average pre - test and post -test. Differences can be seen in the average post-test about the description of the original 89.25 65.75 . Then the use of video media facilitate students in understanding the concept of static electricity so that there is a significant improvement effect on students’ understanding of the process after the use of video as a medium lightning physics learning materials static electricity. Keywords: Video ; lightning ; Media Learning Physics ; Static electricity.